Insect Pest Management of Vegetables in Pocket Areas of Modi Rural Municipality, Parbat - Gautam, Prem Raj; Sharma, Som (Prithvi Journal of Research and Innovation, 2021)
Modi Rural Municipality is one of the commercial vegetable pocket areas under temperate climate. A study was carried out during July 2021 in three vegetable growing areas: Tilahar, Deupur and Bajung of Modi Rural Municipality. A total number of nine quadrates (10×10) m2 were laid, including three replicating quadrates in each area with 500m differences from each quadrates in the sampling site. Overall, 18 farmers were interviewed to collect information about vegetables grown, insect pests that affected vegetables and their management practices. The total number of 24 insect pests were recorded belonging to five orders from 14 vegetable crops. Greater Sorensen's similarity index of insects was recorded in Tilahar and Deupur (ß=0.52) because there was similarity in environment, habitats, larval host plants and visiting plants of insects. Lower Sorensen's similarity index (ß=0.25) was recorded in Deupur and Bajung as there was less similarity in environment, habitats, larval host plants and visiting plants of insects. Insect pests and diseases on vegetables were the major problems in the study areas. The use of chemical insecticides was the means to control adopted by most of farmers while a few of them used other control methods. Insecticides on pests were applied considering fewer precautions. The study clearly indicated that the farmer’s knowledge towards Integrated Pest Management (IPM) was null and thus necessary action should be taken by concerned agencies to increase rate of vegetable production, avoid the heavy use of chemicals and allied consequences.